2016
DOI: 10.1016/j.ajpath.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Dysfunction in Pneumocystis-Associated Pulmonary Hypertension Is Related to Endothelin Response and Adrenomedullin Concentration

Abstract: Pulmonary hypertension subsequent to an infectious disease can be due to vascular structural remodeling or to functional alterations within various vascular cell types. In our previous mouse model of Pneumocystis-associated pulmonary hypertension, we found that vascular remodeling was not responsible for observed increases in right ventricular pressures. Here, we report that the vascular dysfunction we observed could be explained by an enhanced response to endothelin-1 (20% greater reduction in lumen diameter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In animal models, it has been shown that the immune response to an infectious agent, such as Pneumocystis , can lead to later development pulmonary hypertension (PH) that persists after the pathogen has been cleared (4, 5). In this model of Pneumocystis -associated PH there are a substantial enhancement of the vasoconstrictor response to endothelin-1 and marked reduction in production of adrenomedullin an important vasodilator (6).…”
Section: Introductionmentioning
confidence: 98%
“…In animal models, it has been shown that the immune response to an infectious agent, such as Pneumocystis , can lead to later development pulmonary hypertension (PH) that persists after the pathogen has been cleared (4, 5). In this model of Pneumocystis -associated PH there are a substantial enhancement of the vasoconstrictor response to endothelin-1 and marked reduction in production of adrenomedullin an important vasodilator (6).…”
Section: Introductionmentioning
confidence: 98%